Comprehensive T‐cell immunophenotyping and next‐generation sequencing of human papillomavirus (HPV)‐positive and HPV‐negative head and neck squamous cell carcinomas. Issue 3 (6th October 2017) - Poropatich, Kate; Fontanarosa, Joel; Swaminathan, Suchitra; Dittmann, Dave; Chen, Siqi; Samant, Sandeep; Zhang, Bin
Abstract: The success of programmed cell death 1 (PD‐1) inhibition in achieving a clinical response in a subset of head and neck squamous cell carcinoma (HNSCC) patients emphasizes the need to better understand the immunobiology of HNSCC. Immunophenotyping was performed for 30 HCSCC patients [16 human papillomavirus (HPV)‐positive; 14 HPV‐negative] on matched tissue from the primary tumour site, locally metastatic cervical lymph nodes (LNs), uninvolved local cervical LNs, and peripheral blood. CD4 + and CD8 + T‐cell lymphocytes obtained from tissue were analysed for expression levels of the inhibitory receptors PD‐1, TIM‐3 and CTLA‐4. Next‐generation sequencing of the T‐cell receptor (TCR) β chain was performed on patients ( n = 9) to determine receptor repertoire diversity and for clonality analysis. HPV‐negative HNSCC patients, particularly those with stage IV disease, had significantly higher proportions of CD8 + T cells expressing CTLA‐4 in tumour tissue ( P = 0.0013) and in peripheral blood ( P = 0.0344) than HPV‐positive patients, as well as higher expression levels of TIM‐3 + PD‐1 + CD8 + T cells ( P = 0.0072) than controls. For all patients, PD‐1 expression on CD8 + T cells – particularly in HPV‐negative HNSCC cases – strongly correlated ( r = 0.63, P = 0.013) with tumour size at the primary site. The top CD8 + TCR clones from tumour tissue significantly overlapped with circulating peripheral blood TCR clones ( r = 0.946), and HPV‐positive patients had frequently expanded TCR clones that were more hydrophobic – and potentially more immunogenic – than those from HPV‐negative patients. Collectively, our findings demonstrate, for the first time, that high‐stage HPV‐negative HNSCC patients with primary tumours at different sites in the head and neck have elevated peripheral CTLA‐4 + CD8 + T‐cell levels, that tumour‐familiar CD8 + T cells are detectable in peripheral blood from HNSCC patients, and that TCRs from HPV‐positive HNSCC patients potentially recognize distinctly immunogenic cognate antigens. However, our findings are preliminary, and need to be further confirmed in a larger patient cohort; also, how these factors affect patient response to immunotherapy needs to be determined. Copyright © 2017 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.